Impact of an information video before colonoscopy on patient satisfaction and anxiety - Mahmut Arabul; Altay KANDEMİR and Mustafa Çelik and Emrah Alper and Zehra Akpınar and Fatih Aslan and Sezgin VATANSEVER and Belkıs Ünsal (Turkish Journal of Gastroenterology, 2019)
-